Poorly differentiated thyroid cancer: Clinical, pathological, mutational, and outcome analysis - Amit Agarwal; Nelson George; Niraj Kumari; Narendra Krishnani; Prabhaker Mishra; Sushil Gupta (Indian Journal of Pathology and Microbiology)
Introduction: Poorly differentiated thyroid cancer (PDTC) remains a challenge not only for pathologists and surgeons because of the difficulties associated with the diagnostic process and the compelling need for difficult thyroidectomy, but it is also of high clinical relevance because it is responsible for mortality in non-anaplastic follicular cell-derived thyroid cancer. Materials and Methods: Cases of PDTC within a 30-year period were reviewed by two independent pathologists. Histological features like atypical mitosis, necrosis, capsular, and vascular invasion were studied. Mutation analysis was done for BRAF, RET/PTC, RAS, and PI3KCA, and P53 was performed using immunohistochemistry. Results: There were 39 patients with a median age of 53 years; 14 patients were more than 55 years of age. At presentation, 38.4% had compressive features and the median tumor size was 9 cm. At presentation, 67.7% had an extrathyroidal extension (ETE). R0 resection was achieved in 41%, with 12 cases resulting in a difficult thyroidectomy. Necrosis was seen in 65.7% and mitosis in 73.3% with well-differentiated components in 41%. The commonest mutation was RAS (23.1%). Survival was higher in the operable group (54.26, 95% confidence interval [CI]: 30.83–77.70 vs. 20.25, 95% CI: 0–54.07) months, respectively; however, 10-year survival was only 5% and only the tumor size and presence of mitosis were independent risk factors. Conclusion: PDTC presents with worrisome features like large size, ETE, and rapid growth. Aggressive surgical resection with extended/radical thyroidectomy may result in better loco-regional control and improved survival. RAS was the frequent mutation detected. It is worthwhile to identify prognostic factors that can predict the course of PDTC.